Delayed Chylothorax during Treatment of Follicular Lymphoma with a Malignant Pleural Effusion - Chigozirim N. Ekeke; Ernest G. Chan; James D. Luketich; Rajeev Dhupar (Case Reports in Surgery)
Chylothorax occurs following dysfunction or disruption of the lymphatic drainage along the thoracic duct. Malignant and traumatic causes account for the majority of these occurrences, with lymphoma accounting for 11-37% of chylothoraces. The clinical course of chylothorax may include dehydration, malnutrition, immunosuppression, electrolyte disturbances, infection, and ultimately death. Management of chylothorax is patient-specific and is based on etiology and surgeon experience. Initially, most chyle leaks are managed with nonoperative strategies, such as gut rest, hyperalimentation, and pleural drainage, and, at times, medium-chained fatty acid diet or octreotide, with hopes to decrease chyle production (Zabeck et al. (2011)). High-output chyle leaks following iatrogenic injury or trauma are commonly managed with thoracic duct ligation. Lymphangiography with or without thoracic duct embolization has become increasingly popular and efficacious with the possible benefit of less morbidity (Cope et al. (2002)). We report a case of a 61-year-old male with delayed chylothorax while having an indwelling pleural catheter for malignant pleural effusion during treatment of follicular lymphoma. Percutaneous thoracic duct embolization was attempted but was unsuccessful. Chemotherapy, fluid management, and nutritional support allowed this to resolve over the course of ninety days from diagnosis. We describe the patient’s clinical course and highlight nonoperative management of delayed chylothorax in the setting of follicular lymphoma treatment.